Preventing Racism in Schools: Group Guidance with Mau’izatul Hasanah at MAN 2 Labuhanbatu Utara - Murni, Sheila Natasya; Suryani, Ira (Journal of Social Work and Science Education, 2025)
Schools play a strategic role in shaping character and instilling values of tolerance in the younger generation. However, practices of racism are still found in educational environments, both in the form of hate speech, stereotypical jokes, and the exclusion of certain groups. This study aims to prevent racist behavior at MAN 2 Labuhanbatu Utara through group guidance services using the Mau’izatul Hasanah approach, a method of gentle, persuasive advice based on Islamic values, particularly brotherhood, tolerance, and justice. The research employs a descriptive qualitative approach with purposive sampling techniques targeting guidance counselors and students who exhibit tendencies of racist behavior. Data were collected through observations, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s model. The research results show a significant reduction in discriminatory behavior post-intervention, reflected in the increase of students’ tolerance scores from an average of 55% to 85%. This change includes the avoidance of racist jokes, increased inter-ethnic interactions, and students’ initiatives to reprimand discriminatory behavior. These findings fill a research gap that previously rarely integrated group guidance with an explicit Islamic religious approach. Mau’izatul Hasanah proves to be effective not only in enhancing cognitive awareness but also in forming sustainable inclusive behavior, thus it can serve as a model for character building in multi-ethnic schools.